Bioactive glasses: Special applications outside the skeletal system - Baino, Francesco; Novajra, Giorgia; Miguez Pacheco, Valentina; Boccaccini, Aldo R.; Vitale-Brovarone, Chiara (Journal of Non-Crystalline Solids, 2016)
Bioactive glasses were invented 45 years ago and have been in clinical use since the 1980s in otology, orthopaedics and dentistry. Initially born as bioactive materials to fill bone defects, bioactive glasses expanded their biomedical suitability towards a broad spectrum of tissue engineering and therapeutic applications, and research evolution seems to witness that their potential is far from being fully exploited. Classical applications of bioactive glasses involve bone filling materials and dental implants; however, the fascinating question to be answered in the next few years is: how can bioactive glasses be useful in soft tissue regeneration and to treat diseases, such as tumours, that may affect internal organs? This review paper focuses on research that demonstrates the suitability of bioactive glasses in contact with tissues outside the skeletal system, including muscle and nerve tissue regeneration, treatment of diseases affecting sense organs (eye and ear), embolization of neoplastic tissues, cancer radiotherapy via injectable microspheres, and wound dressing. A prospect for future research is also provided, highlighting the potential associated to targeted therapy via local ion release, angiogenesis stimulation and in situ drug release, as well as the promise of biofabrication for the development of bioactive glass-containing composite constructs for organ regeneration.
Keywords: Angiogenesis; Antibacterial properties; Bioglass; Cancer treatment; Composites